2015
DOI: 10.1177/2050640615612409
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of adenocarcinoma and high-grade dysplasia in patients with non-dysplastic Barrett’s esophagus: Results from a cohort from a country with low esophageal adenocarcinoma incidence

Abstract: Background: The risk of esophageal adenocarcinoma (EAC) in non-dysplastic Barrett's esophagus (NDBE) is considered to be approximately 0.3% per year or even lower, according to population-based studies. Data from countries with low EAC incidence are scarce. Our principal aim was to determine the incidence of high-grade dysplasia (HGD) and EAC in NDBE. Our secondary aims were to identify the predictors of progression and to calculate the incidence of HGD/EAC, by using the calculation method for surveillance tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Some recent guidelines have excluded patients with a segment length < 1 cm for the diagnosis of BE. Given that this is a recent update, we were able to identify only two studies [18,28] that specifically defined SSBE as a length < 3 cm but also excluded patients with a segment length of < 1 cm (i. e. short-segment length being ≥ 1 cm to < 3 cm).…”
Section: Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent guidelines have excluded patients with a segment length < 1 cm for the diagnosis of BE. Given that this is a recent update, we were able to identify only two studies [18,28] that specifically defined SSBE as a length < 3 cm but also excluded patients with a segment length of < 1 cm (i. e. short-segment length being ≥ 1 cm to < 3 cm).…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…A meta-analysis by Desai et al in 2012 reported an annual EAC incidence rate of 0.33 % in patients with NDBE, but did not provide a comparison between SSBE and LSBE patients [10]. More recently, observational studies have been published comparing the risk of progression between these two patient groups, but precise estimates have varied [17,18]. Our aim was to perform a systematic review and meta-analysis of published studies to provide a more accurate estimate of the risk of neoplastic progression in NDBE patients based on the length of the BE segment.…”
mentioning
confidence: 99%
“…Supporting this concept, the annual risk of progression to EAC is higher in HGD (6.0-7.0%) 18,19 compared to community LGD diagnoses (0.4-0.6%) 20,21 or non-dysplastic BE (0.1-0.3%, which has decreased in recent decades from previous higher estimated ranges). [22][23][24][25][26][27] Data suggest superior survival outcomes when EAC is diagnosed in pre-existing BE. In a study based on Surveillance, Epidemiology, and End Results and linked Medicare data, patients diagnosed with EAC in the setting of pre-existing BE had overall lower stage EAC and superior overall survival compared to those diagnosed with EAC without pre-existing BE (hazard ratio, 0.56; 95% CI, 0.50-0.61 that persisted in an adjusted model with hazard ratio, 0.72; 95% CI, 0.65-0.80).…”
Section: Clinical Value Of Screeningmentioning
confidence: 99%
“…The term "long segment BE" is defined as the length of columnar mucosa >3 cm, and "short segment BE" is used when the length is between 1 and 3 cm. Increased length of columnar mucosa is associated with increased incidence of intestinal metaplasia and about 46% increase in the risk of cancer progression for every 1 cm increase in the BE length [13]. For BE diagnosis, the American College of Gastroenterology (ACG) recommends four random biopsies every 2 cm, or 8 random biopsies to maximize the yield of intestinal metaplasia on histology.…”
Section: Histopathology Of Bementioning
confidence: 99%